Scientific Research Methodology - Biju Dharmapalan (Narosa Books, 2012)
SCIENTIFIC RESEARCH METHODOLOGY is an introductory text explaining various aspects of research methodology and communication in science. The basic philosophy of science is based on the fundamental assumption that scientific experiment is not completed until the results are published. Science is the only profession where one has to do the twin task of doing and writing. All persons practicing science should know how to communicate the results of the research properly in a written format. The book presents an outline of how to write a scientific paper and a thesis. This book is primarily designed for the undergraduate and postgraduate students of various science subjects; it would also be useful to doctoral students as well as teachers.